2021
DOI: 10.1038/s41386-021-00988-6
|View full text |Cite
|
Sign up to set email alerts
|

A normative chart for cognitive development in a genetically selected population

Abstract: Certain pathogenic genetic variants impact neurodevelopment and cause deviations from typical cognitive trajectories. Understanding variant-specific cognitive trajectories is clinically important for informed monitoring and identifying patients at risk for comorbid conditions. Here, we demonstrate a variant-specific normative chart for cognitive development for individuals with 22q11.2 deletion syndrome (22q11DS). We used IQ data from 1365 individuals with 22q11DS to construct variant-specific normative charts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Comparisons to the normative sample confirmed that children with 22q11.2 CNVs have statistically significantly lower language scores in relation to typically developing peers, which is in accordance with results based on parental reports [ 13 ]. In addition, a shift of approximately −2 SD in the 22q11.2DS group is consistent with findings on their cognitive profiles in previous studies [ 53 , 54 , 55 , 56 ]. We found a shift of approximately −1.5 SD in the 22q11.2Dup group, which is at the lower end of the range of their cognitive capabilities based on previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Comparisons to the normative sample confirmed that children with 22q11.2 CNVs have statistically significantly lower language scores in relation to typically developing peers, which is in accordance with results based on parental reports [ 13 ]. In addition, a shift of approximately −2 SD in the 22q11.2DS group is consistent with findings on their cognitive profiles in previous studies [ 53 , 54 , 55 , 56 ]. We found a shift of approximately −1.5 SD in the 22q11.2Dup group, which is at the lower end of the range of their cognitive capabilities based on previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The distribution of IQ scores, subdivided in full scale IQ (mean = 66.1, SD ± 10.4), verbal IQ (mean = 72.3, SD ± 12.4) and performance IQ (mean = 68.5, SD ± 11.2) was slightly skewed to the left compared to the normal distribution representative of 22q11.2DS patients as a whole [ 33 , 34 ] (Supplementary Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, again, findings in 22q11DS may provide helpful guidance for our understanding of the mechanisms underpinning these same phenomena in the context of other genetic variants. As discussed here, these likely include genetic variation in the rest of the genome, encompassing the modifying impact of both rare and common variants [98,99], environmental effects, and variation resulting from stochastic events during brain development. Animal models of 22q11DS have indeed shown that genetic background, as well as environmental and stochastic developmental effects modulate phenotypic expression and have pleiotropic effects [40,109,[166][167][168].…”
Section: Discussionmentioning
confidence: 99%
“…22q11DS, with an average of 70, is shifted approximately 30 points (or 2 standard deviations) to the left compared to the general population [99]. Similarly, while the penetrance of SSD and ASD diagnoses in 22q11DS is 25% and 10-40%, respectively, various studies have observed that the proportions of individuals with subclinical manifestations of both conditions are substantially higher [107,125].…”
Section: Variable Penetrance and Expressivitymentioning
confidence: 99%
See 1 more Smart Citation